A Comprehensive Analysis of Efficacy, Cost-Effectiveness, and User Perception for Implementing Automated Attendance Systems in Educational Institutions in Sinaloa, Mexico - Montoya Leyva , Miguel Angel; Atondo Osuna, Jesus Francisco; Higuera Quintero , Claudia Jacive; Cabrera Montoya , Santa Xiomara (Technium: Romanian Journal of Applied Sciences and Technology, 2026)
Given the continued use of manual procedures for attendance registration and the persistence of compartmentalized views in the assessment of technological solutions, this work proposes a comprehensive and integrated evaluation of three fundamental axes: technical performance, financial sustainability, and user perception. Based on a systematic review of the academic corpus and the analysis of contextual information regarding the state of Sinaloa, Mexico, it is identified that feasibility depends on the harmonization of these elements. The findings reveal that, in environments subject to budgetary and infrastructural constraints, RFID-based platforms emerge as the most robust and enduring option, notable for their high accuracy, low cost threshold, autonomous operation without permanent connectivity, and a higher degree of acceptance within the educational community. Thus, the central contribution lies in a holistic evaluation framework that transcends partial analyses and provides a contextualized decision-making tool for selecting technologies aligned with the specific conditions of each institution